Odpowiedzi

2010-01-19T16:20:58+01:00
1)
3x-y=5
6x-2y=10
-y=5-3x /*(razy) -1
6x-2y=10
y= -5+3x
6x-2(-5+3x)=10
y= -5+3x
6x+10-6x=10
y= -5+3x
0=0 układ nieoznaczony
2)
3x-y=5
2x+2y=6
-y=5-3x /*(razy) -1
2x+2y=6
y=5-3x
2x+2(5-3x)=6
y=5-3x
2x+10-6x=6
y=5-3x
4x=-4/:4
y=5-3x
x=-1
y=5-3(-1)
x=-1
y=5+3
x=-1
y=8 uklad oznaczony
2010-01-19T16:24:19+01:00
1)
3x-y=5
6x-2y=10
-y=5-3x / * (-1 )
6x-2y=10
y= -5+3x
6x-2(-5+3x)=10
y= -5+3x
6x+10-6x=10
y= -5+3x

2)
3x-y=5
2x+2y=6
-y=5-3x / * ( -1 )
2x+2y=6
y=5-3x
2x+2(5-3x)=6
y=5-3x
2x+10-6x=6
y=5-3x
4x=-4/:4
y=5-3x
x=-1
y=5-3(-1)
x=-1
y=5+3
x=-1
y=8